The Influence Of Recruitment, Training, And Work Motivation In Improving Employee Performance At PT. Perkasa Internusa Mandiri - Siagian, Jonatan Pebrianto; Insan, Muhammad Yalzamul; Yanti, Eli Delvi (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of recruitment, training, and work motivation on employee performance at PT. Perkasa Internusa Mandiri. This study uses a quantitative approach with a survey method of 80 employees which is also used as a sample. Data were collected through questionnaires and analyzed using multiple linear regression with the help of the SPSS program. The results showed that recruitment had a regression coefficient (B) of 0.187 with a t-value of 1.909 and a significance of 0.060, so that it had a positive but insignificant effect on employee performance. The training has a regression coefficient (B) of 0.538 with a t-value of 4.821 and a significance of 0.000, which means that it has a positive and significant effect on employee performance. Work motivation has a regression coefficient (B) of −0.283 with a t-value of −2.968 and a significance of 0.004, so that it has a negative and significant effect on employee performance. The results of the simultaneous test showed an F value of 27.253 with a significance of 0.000, which indicates that recruitment, training, and work motivation together have a significant effect on employee performance. A determination coefficient value (R²) of 0.518 indicates that 51.8% variation in employee performance can be explained by the research model. Training is the most dominant variable in improving employee performance.